The ileal microbiome and mucosal immune profiles in response to dietary supplementation of ultra-grinded Astragalus membranaceus in weaned goats - Luo, Guowang; Gebeyew, Kefyalew; Zhou, Chuanshe; Tan, Zhiliang; Yang, Wenzhu; Niu, Dongyan; Ran, Tao; Liu, Yong (Frontiers in Microbiology, 2023)
Weaning goats are susceptible to diarrhea and have weakened immune functions due to physiological, dietary and environmental stresses. Astragalus membranaceus (A. membranaceus), a traditional Chinese medicinal herb, has been shown to improve growth performance and immunity in weaned ruminants. However, the influence mechanism of A. membranaceus on intestinal microbiota and mucosal immunity in weaned goats is still unknown. This study investigated the effects of ultra-grinded A. membranaceus (UGAM) on the immune function and microbial community in the ileum of weaned goats. Eighteen healthy weaned Xiangdong black goats (BW, 5.30 ± 1.388 kg) were used in a study of completely randomized block design with 28 days long. The animals were randomly assigned to either a basal diet supplemented with 10 g/d of milk replacer (CON, n = 9) or the CON diet supplemented with 10 g/head UGAM (UGAM, n = 9). Supplementation of UGAM increased (P < 0.05) the plasma concentrations of total protein and albumin. Meanwhile, the addition of UGAM reduced (P < 0.05) the relative mRNA expression of the IL-6 gene (a marker of inflammation), indicating the potential immunomodulatory effect of UGAM. Moreover, the relative abundances of Verrucomicrobiota and Mycoplasma were lower (P < 0.05) in the ileum of goats supplemented with UGAM than CON. These findings suggest that dietary supplementation of UGAM may have enhanced the ileum health of weaned goats by reducing inflammation factor expression and reducing the relative abundance of pathogenic microbes. The observed beneficial effects of ultra-grinded A. membranaceus on ileal mucosal immune and the community of ileal microbiota indicate its potential to be used as a viable option for promoting the well-being of weaned goats under weaning stress.